Keadilan dan Transparansi dalam E-Commerce: Menghadapi Tantangan Ekonomi Digital dengan Prinsip Syariah - Fata, Zainol; Hofifah, Hofifah (Journal of Islamic Economics Studies and Practices, 2025)
The approach used in this study focuses on the analysis of Justice and Transparency in E-Commerce, especially in the context of facing the challenges presented by the digital economy based on sharia principles. In this paper, the development of interactions between individuals and groups is used as the main analysis tool. This work is the result of a research process that focuses on literature studies. After conducting the research, it can be concluded that e-commerce has great potential to drive the growth of the digital economy, but challenges in terms of justice and transparency must be overcome so that the benefits can be felt by all parties. By applying the principles of Islamic economics, e-commerce can develop into a more ethical, equitable, and sustainable business ecosystem. Synergy between the government, business actors, and consumers is needed to create an e-commerce system that is in accordance with sharia values ??and provides benefits to the entire community.